GAMBARAN PENGETAHUAN KELOMPOK TANI TERHADAP BAHAYA GIGITAN TIKUS PENYEBAB RAT BITE FEVER DAN UPAYA PERTOLONGAN PERTAMA - Salsana Billa, Frida Ayu; Kusumarini, Shelly; Lestari, Putri Dwi; Annadhifa, Chandra Luki; Zuhria, Farida Puspita (Universitas Nusa Cendana, 2022)
ABSTRACT. House rats (Rattus tanezumi) are mammals from the order Rodentia (rodents) that have incisors that continue to grow in each upper and lower jaw which require them to bite or chew many objects to control their long teeth. Rat Bite Fever (RBF) is a disease caused by rats (Rattus tanezumi). The purpose of this activity is to determine the level of knowledge and understanding of the people of Pucakwangi, Babat, Lamongan villages before and before the socialization. This activity was carried out in an exploratory qualitative manner on 20 family heads, members of the Pucakwangi Village Farmer Group. An exploratory approach to explore more factors that are closely related to the application of first aid in the case of rats to 20 members of the Kelompok Tani Desa Pucakwangi which involves experience and them. the survey results obtained that often meet with rats in the vicinity of the residence, as well as knowing the results of rat research. Basically all members of the Pucakwangi Village Farmer Group can be taught to start a new habit well, namely the practice of cleaning the home environment and being able to become a doctor themselves or family members if an injury occurs due to rats. Based on the results of the evaluation, the success rate of socialization on the dangers of rats and efforts to prevent RBF and first aid is 90%. Keywords: house rat’s; rat bite; rat bite fever; first aid